Long-Covid19 Symptoms After Infection in Covid Long-Haulers. - Stefania Pellino; Luciano, Margherita; Luciano, Rosamaria; Erika Mancini; Maria Concetta Conte; Gennaro Volpe; Tommaso Zerella (British Journal of Healthcare and Medical Research, 2023)
The negative molecular swab does not mean that the body and mind are healed: even months after Sars-Cov-2 infection, patients may continue to have symptoms. The symptoms mainly present at 6-12 months in patients recovered from Covid-19 are: asthenia, breathlessness, difficulty in breathing deeply, myalgia but also psychological disorders and difficulty in concentrating such as “brain fog”. The study was conducted from June 2021 to July 2021 at Health Prevention Department in Benevento (Campania Region, South Italy). 133 patients accepted the questionnaire in the form of telephone interview. The purpose of this study is precisely to highlight how, although a year after infection, a number of patients still show post-COVID symptoms. In particular 77 of 133 positive patients are resulted Long-Haulers (58%).